(untitled) (Global Journal of Management and Business Research, 2019)
This research is examining the effect of experiential marketing and word of mouth with satisfaction as an intervening variable on GO-JEK customers in Mataram. The type of research conducted is an associative casualty. The sample design uses non-probability sampling and the accidental sampling technique is used to determine to sample with an unknown population. The sample taken was GO-JEK customers in Mataram, which amounted to 100 samples. Data analysis uses path analysis with the smart PLS program. The Results Showed that experiential marketing had a positive and not a significant effect on word of mouth, experiential marketing had a positive and significant effect on satisfaction, and satisfaction had a positive and not a significant effect on word of mouth GO-JEK customers in Mataram. Then word of mouth is influenced by experiential marketing with satisfaction mediation. In general Go-JEK still needs to introduce its products to the community in Mataram City.